Numerical Study of Stress Distribution in Soft Clay Treated with Stone Column - Al-Waily Maki J. M.; Al-Qaisi Maysa S. (E3S Web of Conferences, 2023)
This study used a finite element analysis approach employing Plaxis 3D to analyze the stress concentration ratio, a critical parameter in geotechnical engineering, to examine stresses operating on stone columns and soft soils. This study also looked at the effect of the stiffness ratio between the stone column and the neighboring soil. With the same length and three different diameters, 0.8 m, 1.0 m, and 1.2 m, or three area replacement ratios ranging from 7% to 16%, respectively, floating and end-bearing stone columns were used. The influence of soft soil undrained cohesion, cu ranging from 6 kPa to 40 kPa, was also considered in the current study. The stiffness ratio for columns to adjacent soil, end bearing or floating stone column, and area ratio all have a significant impression on the performance of the stone column in treating soft soil and stress transmission mechanisms in the enhanced soil body, according to parametric studies. The average stress concentration ratio in soil improved with an end-bearing stone column of φ= 35° and raised to 2.63 and 4.71 at φ = 50°, ranging from 1.41 to 2.35 for area replacement ratios of 7% and 16%.